Keberkesanan program pembangunan keusahawanan terhadap niat keusahawanan pelajar Kolej Komuniti, Kementerian Pendidikan Tinggi Malaysia - Zairon, Mustapha (2018)
The field of entrepreneurship is fast developing in line with the government support for Malaysians to adopt entrepreneurship as their career choice. Despite a good development of entrepreneurship courses and programs in higher education, doubts about the effectiveness of formal entrepreneurship education continue to rise. Previous research has shown that intention is the main contributing factor that motivate individuals to engage in entrepreneurship. Entrepreneurship education programs have been carried out extensively at higher education levels with the aim of giving the widest possible exposure so that students have a positive attitude towards entrepreneurship. Previous researches were found to be lack of a strong theoretical orientation; variables were examined in isolation and with no clear theoretical rationale. This study aims to assess the effectiveness of entrepreneurial development programs at on entrepreneurial intention among students at Malaysian community colleges by applying Ajzen's Entrepreneurial Intentional Model constructs, personality traits, and demographic factors. The study also examines the mediating effect of these constructs on the relationship between entrepreneurial development programs and entrepreneurial intention. Data were collected through a survey which involved a total sample of 1277 community college students. Partial Least Squares Structural Equation Modeling was used to test the hypothesized relationships. The main findings of this study provide empirical support that Ajzen's Entrepreneurial Intentional Model constructs and personality traits play a critical mediating role in explaining the effect of entrepreneurial development programs on entrepreneurial intention. The findings provide a better understanding of the theoretical mechanism linking these main constructs. Theoretical and managerial implications of the findings and suggestions for further research are also discussed in this study.